The SIJORI Growth Triangle: Progress, Problems and Prospect - Xu Xiaodong (Journal of Maritime Studies and National Integration, 2019)
The Singapore-Johor-Riau Growth Triangle established in the late 1980s is the first regional cooperation framework in Southeast Asia. However, such a promising framework ran into a dilemma after ten years of development. Main factors accounting for its unanticipated limited progress include uneven regional economic performance, divergent individual interests at all levels, rising social problems, and uncertain external environment. A thorough review of the growth triangle with special attention on the progress as well as the issues be inspiring for the further promotion of the regional cooperation, which requires dynamics both internal and external. The first category of dynamics includes the design of a unified administrative institution, coordination between public and private sectors, more liberal policies, the proper understanding of social and knowledgeable elements, the role of overseas Chinese and the utilization of historical legacies. The other category mainly underlines utilizing external stimuli outside the region, especially China’s Maritime Silk Road Initiative (MSRI).